Efektivitas Pelaksanaan Ketentuan Upah Minimum Bagi Pekerja Berdasarkan Undang-Undang Nomor 6tahun 2023 Tentang Cipta Kerja - Niken Rahmawati Putri; Diky Dikrurahman (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the effectiveness of the implementation of the provisions regarding the provision of minimum wages to workers based on Law Number 6 of 2023 concerning Job Creation and analyze the factors that influence its implementation effectiveness. This study uses an empirical juridical method, namely research that combines secondary data (statutory regulations/theory) with primary data obtained directly from the field. The results show that the provision of minimum wages is clearly regulated in Law Number 6 of 2023 concerning Job Creation and its implementing regulations. However, its implementation is not yet fully effective because violations of below-minimum wage payments are still found. The effectiveness of the implementation of minimum wage provisions is influenced by legal substance, legal structure and legal culture. Consequently, reinforcing institutional oversight and law enforcement, along with enhancing the legal awareness of all parties involved, is essential to ensure that workers' rights to the minimum wage are fulfilled pursuant to the prevailing laws.